2,4-Dichloro-N-(4-methylphenyl)benzenesulfonamide - B. Thimme Gowda; Sabine Foro; P. G. Nirmala; Hartmut Fuess (Acta Crystallographica Section E, 2010)
The title compound, C13H11Cl2NO2S, crystallizes with four independent molecules in the asymmetric unit. In each of the four molecules, the conformation of the N—C bond in the C—SO2—NH—C segment is gauche with respect to both S=O bonds. The molecules are twisted at the S—N bonds with C—SO2—NH—C torsion angles of 60.6 (4), −59.7 (3), 63.9 (4) and 53.0 (4)°. The benzene rings in two of the molecules are disordered with multiple positions resolved in each case. The crystal structure features inversion dimers linked by pairs of N—H...O hydrogen bonds for each of the four molecules.